The Routledge Handbook of Gender and Sexuality in Byzantium - Messis, Charis; Messis, Charis; Meyer, Mati (Taylor & Francis Routledge [Imprint], 2024)
This Handbook is the first to consider the interrelated subjects of gender and sexuality in the Eastern Roman Empire from an interdisciplinary perspective. Drawing on both modern theories and Byzantine perceptions, and considering multiple periods and religions (Eastern Orthodox, Islamic, and Jewish), it provides evidentiary textual and visual material support for an analysis of the two linked themes. Broadly, the essays demonstrate that gender and sexual constructs in Byzantium were porous. As a result, they expand our knowledge of not only how sex and gender were conceived and performed but also how ideas and practices shaped Byzantine life. The Routledge Handbook of Gender and Sexuality in Byzantium will be an indispensable guide for students and scholars of late antique and Byzantine religion, history, culture, and art, who will find it a useful critical survey of current scholarship and one that shines new light in their areas of research. The focus on issues of gender and sexuality may also be of interest to individuals concerned with Eastern Mediterranean culture, as well as to the broader public. Chapter 21 of this book is freely available as a downloadable Open Access PDF at http://www.taylorfrancis.com under a Creative Commons Attribution-Non Commercial-No Derivatives (CC-BY-NC-ND) 4.0 license.
eng
Keywords: History and Archaeology; History; Byzantium; culture; gender; history; sexuality